Phenomenological model of information operation in social networking services - Kateryna Molodetska; Yuriy Tymonin; Oleksandr Markovets; Andrii Melnychyn (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In modern conditions, social networking services have become the users’ leading channel of communication, which are called actors. Therefore, social networking services are used by intruders to gain benefits in the information space of virtual communities for further influence on political and social processes in the state. In the article the phenomenological model of information operation in social networking services is developed. The model allows to take into account the processes of development of social networking services through the formation of new relationships between actors and the formation of virtual communities. At the same time, behind the model are the processes of degradation of social networking services that are associated with the dissipation of content. The developed model is used for experimental research of real information operation in social networking services. The obtained results will increase the efficiency and effectiveness of counteracting the threats to information security of the state in social networking services by the relevant departments.